Contributions From Psychology to Effectively Use, and Achieving Sexual Consent - Flecha, Ramon; Tomás, Gema; Vidu, Ana (Frontiers in Psychology, 2020)
Psychology related to areas such as gender, language, education and violence has provided scientific knowledge that contributes to reducing coercive social relationships, and to expanding freedom in sexual-affective relationships. Nonetheless, today there are new challenges that require additional developments. In the area of consent, professionals from different fields, such as law, gender, and education, are in need of evidence differentiating human communication that produces consent, and those conditions that coerce. Up to now, consent has been focused on verbal language, for example, “no means no,” or “anything less than yes is no.” Despite the fact that focusing consent on verbal language is a very important part of the problem, it does not solve most of the issues currently raised, like the famous case of “La Manada” in Spain. This article presents the most recent results of a new line of research, which places the problem and the solution in communicative acts, not only in speech acts. Even though there might be a “yes” in a sexual-affective relationship, there might not be consent, and it is indeed a coercive relationship if that “yes” has been given in a relationship determined by institutional power or by interactive power. Institutional power may occur if whoever made the proposal for the relationship is a person in charge of the process of selecting personnel in a company, and one of the candidates is the person who receives the proposal. Interactive power may occur if whoever makes the proposal is situated in an equal or inferior position in the company to the person receiving it, but the former threatens sextortion the latter. The potential social impact of this research has been already shown in the cases analyzed for this study.